(untitled) (Research, Society and Development, 2021)
Anxiety is considered increasing in modern society and related to academic life, especially students submitted to performance evaluations to prove good performance. The objective of this study was to determine the prevalence of anxiety in the period of academic performance evaluations, among students of the Pharmacy course of a private University in the city of São Paulo, Brazil. The study was conducted with 276 Pharmacy undergraduates, with an average age between 18 and 27 years (67%), single (59.8%) and female prevalence (74.6%). Students, before performance assessments, reported anxiety alone (64.5%) or associated with stress, worry, insomnia and impatience (63%). There was a statistically significant difference between anxious (16.9±12.2) and quiet (3.6±2.9) students before performance evaluations, with p<0.001. After the performance evaluations, 50% of the students reported concern alone and the association of concern with impatience, stress and insomnia was reported by 10.1%. Regarding the habit of studying, 49.3% ​​reported that they studied when there was time and 45.3% reported studying frequently. This paper shows that entering academic life is marked by changes in responsibilities and the choice of a profession, accompanied by anxiety and concerns related to good performance, suggesting the need for the adoption of institutional policies for anxiety prevention.